Effects of Pandemic Covid 19 on Indonesia Banking - Pandu Adi Cakranegara (Yayasan Ilomata, 2020)
The Covid 19 pandemic befell the world and Indonesia was no exception. This pandemic affects not only health but also socio-economic. When the economy is hit then the banking sector is also hit. This study attempts to look at the effects of the Covid 19 pandemic and compare it with the 1998 monetary crisis. By comparing these two crises we can see the differences and similarities of the current crisis. But the most important thing is how regulators and banking can draw lessons from the 1998 crisis to be applied to the current crisis. This research is applicative research that is by applying the existing framework to a new situation. The framework used in this study is a seven-tier system in managing bank assets and liabilities. From the results of this study can be seen the fundamental differences between the crisis of Pandemic Covid 19 and the monetary crisis of 1998. This study concludes that the banking conditions in Indonesia are currently more resistant to crisis. However, government support, especially in the adoption of macroeconomic policies, is still needed to maintain economic stability.